ANALISIS KEAMANAN DATA SISTEM INFORMASI DI PUSKESMASPLERET BANTUL YOGYAKART - Hendri Nurvianto Saputra; Jamroni Jamroni (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2017)
Background: Server is a computer system providing various services which can be accessed by client computer that is connected to the network. Server is used to keep data needed client computer. Server data management system information public health center in public health center Pleret Bantul stores saves services patient data and contains public health center's report consist of public health center visiting report, work unit report, health provile report. Sinse server data uses computerization system so that the data is suspectible of broken or lost. In maintaining security data public health center Pleret Bantul assign a password as the only autentikasion the server security system. That's way public health center information and patient data have to be maintain the security system. Objective: The purpose of this research was to know the system security on management system information public health center server data in public health center Pleret Bantul. Method: This research used qualitative with the methods research descriptive. Collecting data should be conducted through primary data which was obtained by live interview way and observation, secondary data was obtained through documentation study that deals with the theme of the research. An interview was conducted by to 4 people who are the informer. Result: there was not permanent procedure system security of server data in public health center Pleret Bantul and the implementation of safety system is done y using password. Officers public health center knowledge about the security system was good but in the implementation or his application users still hasn’t spearheading it well. The attitude of the officers were still not good and less liable in the provision of a password because there was no supervision. The efforts made public health center in dealing with the security system back-up data, server the coordinator of information system management public health center, following the training care and the use of information system management public health center held by the department of health district.